THE RELATIONSHIP OF OCCUPATIONAL SAFETY CLIMATE WITH OCCUPATIONAL SAFETY CLIMATE BEHAVIOR ON POTENTIAL HAZARDS AT RSUD BATARA GURU BELOPA - Hardin Hardin (STIKes Karsa Husada Garut, 2023)
Work safety climate is an aspect that can shape work safety behavior in an organization. This study aims to analyze the relationship between work safety climate and nurses' work safety behavior on potential hazards at Batara Guru Belopa Hospital. The method used in this study was cross sectional, with a sample size of 91 executive nurses. The sample determination used proportionate random sampling technique. Data were collected using a questionnaire with a Likert scale. Data were analyzed univariately and bivariately using the Chi Square test. The results showed that there was a relationship between work safety climate and work safety behavior. Among the seven dimensions of occupational safety climate studied, those significantly related were security prioritization, management commitment and expertise (p=0.006) and strengthening management security (p=0.045). Other dimensions such as administrative security laws, commitment to employee safety, employee priority not to accept risk, communication safety, learning and trust in coworker safety, and employee confidence in the effectiveness of the security system proportionally have a relationship but based on statistical tests do not have a significant relationship.The main element of the work safety climate that can shape work safety behavior is management, with a high commitment and priority from management in the form of initial planning and clear goals for safety, as well as management empowerment and authority by designing a safety system that can be applied by nurses and will be able to move nurses to commit to being involved in building work safety through the application of good work safety behavior.